Creation of an Online Library Instruction Course for Faculty - Zerr, Diane; Maddison, Tasha (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2021)
Librarians at Saskatchewan Polytechnic developed an online information literacy course, created through interdepartmental collaboration, to be completed by new faculty as part of the Adult Teaching and Learning program. Changes to the academic model coupled with mandatory assessment of program development necessitated a major revision of the introductory course, transitioning to a blended learning methodology. As part of this revision, librarians were asked to create an online course to replace some of the content that was formerly offered in face-to-face sessions. Librarians began with the creation of an instructional plan using Bloom’s Taxonomy, learning outcomes, learning steps, and assessments to create an interactive introduction to research and writing. After implementation, the librarians assessed the blended learning approach. The online course content was adjusted and it continues to be reviewed and revised based on participant feedback. The overall process for the development of this online course can be used as an example to guide other librarians’ online delivery of information literacy creating authentic learning experiences.